Experimental approaches for gene regulatory network construction: The chick as a model system. Issue 5 (19th December 2012) - Streit, Andrea; Tambalo, Monica; Chen, Jingchen; Grocott, Timothy; Anwar, Maryam; Sosinsky, Alona; Stern, Claudio D.; Burt, David W.; Farlie, Peter G.
<x xml:space="preserve">Abstract</x> Setting up the body plan during embryonic development requires the coordinated action of many signals and transcriptional regulators in a precise temporal sequence and spatial pattern. The last decades have seen an explosion of information describing the molecular control of many developmental processes. The next challenge is to integrate this information into logic "wiring diagrams" that visualize gene actions and outputs, have predictive power and point to key control nodes. Here, we provide an experimental workflow on how to construct gene regulatory networks using the chick as model system. genesis 51:296–310, 2012. © 2012 Wiley Periodicals, Inc.